ANALISIS FAKTOR – FAKTOR PELAYANAN KARYAWAN FRONTLINER BANK ICB BUMIPUTERA (MNC BANK) KC. TUANKU TAMBUSAI PEKANBARU - Syafri Irwandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine whether the factors of service quality, namely Need for Achievment (n-Ach), Need for Power (n-Pow), Need for Affiliation (n-Affil) effect on the improvement of service by frontline employees of MNC Bank Tuanku Tambusai Pekanbaru. The population in this sample is the entire frontline employees (Teller and Customer Service) MNC Bank. The total numberof samples there are 5 people who made as a respondent, using sampling techniques saturated. Sampling technique when samples taken from the entire members of the population. Based on the analysis of research, it can be drawn some conclusion as follows : service factor that is happening because of the encouragement and motivation of employers and can increase the motivation to earn achievement, responsibilities and task assigned to make employees must master the work, the effectiveness of the team and working comfort is also a trigger factor excellent service.Keyword : Service Excellent, Frontline Employees, MNC Ban